Studying the Effect of Frequency on Dielectric Properties of Cu Powder reinforced Epoxy Composite Material - Jameel, Walaa W. (Nahrain University College of Engineering Journal, 2014)
This paper discussed the effect offrequency on dielectric properties ofdifferent weight fraction of Cu powderreinforced epoxy composite materials.Dielectric properties of epoxy materialwas reinforced with (0, 5, 15, 30, 45) %weight fraction of Cu powder atfrequencies ranges ((50Hz -106Hz) atroom temperature. The results of thisstudy show these dielectric constants anddielectric losses factor were increasedwith increasing in weight fraction due tointerfacial polarization. The results also,exhibit that dielectric constant (?) anddielectric loss factor (?”) decreased withincreasing of frequency account ofelectric polarization changed with anelectric field changed.